Commentary on Place Spirituality: An Islamic perspective. (March 2019) - Latifa, Rena; Hidayat, Komaruddin; Sodiq, Akhmad
If Place Spirituality is considered as an attachment experience to a geographic place or an "object, " for Muslims this concept can be explained by the sharia or Islamic law. However, in the highest level of experience as a Muslim, one may attach to God everywhere and at all times, without consideration of any place, time, or object. This experience can clearly be understood with the explanation of the three levels (spiritual path) for Muslims: (1) sharia or "conceptual knowledge, " (2) tariqa or "experiential knowledge, " and (3) ma'rifa or "divine spiritual experiences" or "spiritual consciousness". At the first and second levels, one may have a Place Spirituality, while at the third level the understanding of and connection to God might be enhanced, and the experience to connect to God can be everywhere, all the time.